The role of Tamil television in maintaining cultural and psychological connections among selected Sri Lankan Tamil immigrants in Toronto Canada - Thevaraj, Fredrick Anton
" This study aimed to find out how Tamil television in Toronto was used by the Tamil immigrants as a tool to maintain their cultural and psychological connections to Sri Lankan Tamils, special emphasis was given to the roles and contributions of Tamil television to ease Sri Lankan immigrants' homesickness. Tamil immigrants in Canada patronize Tamil television, despite the existence of choices provided by other channels. Using the Used and Gratification approach it was found out that the Tamil immigrants in Toronto are an active audience and they choose media in order to meet their cultural and psychological needs. This study used the qualitative approach to research because the problem required the investigation of the participant' lives, as well as their cultural, psychological and social needs. The qualitative method used in the study is the interview method which enabled the researcher to generate information from selected Tamil immigrants living in Toronto who were chosen based on their capacity to articulately project themselves on the social, psychological, and cultural level as well as on matters concerning cultural values. Study results show Tamil television plays a significant role in maintaining a life anchored on the cultural and psychological background of the Tamil immigrant in a new environment. Accordingly, Tamil television is primarily a source of information from their country of origin. It is a provider of entertainment and it brings out the Tamil cultural values through the programs. It is used to education, relaxation and companionship and it gratifies the needs of the immigrants. In this way, it is maintaining cultural and psychological connection to Sri Lankan Tamils. Many Tamil immigrants turn to Tamil television as a way to keep the link to their own country while adopting themselves in the host country. Tamil immigrants' reasons for migration, their strong cultural roots and the freedom given by the Canadian Government to run their own media in their own language with full freedom make it possible for them to maintain cultural and psychological needs are fulfilled by the Tamil programs they choose and watch. The long period of existence of Tamil television stations in Toronto and their vision statements indicate that the television stations satisfies the demand of the Tamil immigrants and they try to promote Tamil cultural values through their programs. Though this study is limited to Sri Lankan Tamil immigrants, even the Canadian born Sri Lankans also have been influenced by their parents and elders to maintain their cultural and psychological contentions to some extent."